Exploring Eco-Anxiety with Young Adolescents in Aotearoa, New Zealand: A Mixed Method Study - Hathaway, Jo (Auckland University of Technology, 2022)
Increasing scientific evidence of environmental issues such as climate change, global warming and pollution indicates these events are impacting people both directly and indirectly, and young people are particularly vulnerable to these concerns. There is evidence these issues are bringing a weighty psychological burden across the globe and affecting mental health and wellbeing, particularly in the younger generation as they are faced with the realities of leading this future world in an altered state, as tomorrow’s leaders and decision makers. Using a mixed methods approach, data was collected from 47 participants through an online survey. Utilising the Hogg eco-anxiety scale (HEAS-13) and three open-ended questions, young adolescent participants were assessed about their concerns regarding environmental issues. While there were high levels of concern about their personal impact on the earth, the affective anxiety was at a relatively mild level, with most adolescents feeling some sort of concern on some days over a two week period. It appears that young adolescents are moderately affected by eco-anxiety and environmental issues. They feel a sense of insignificance, anger about inaction, loss and grief, as well as concern about their personal impact on the planet. They also share a sense of hope that solutions and working together can make a difference. Findings indicate that those who are concerned about environmental issues may also be those who are the most active and engaged in pro-environmental behaviours. Ultimately, wellbeing and mental health of young adolescents is of utmost importance. The implications for health professionals are to assist adolescents to better conceptualise eco-anxiety and to provide them with ongoing support by building resilience and instilling a sense of hope in coping with global changes, while also supporting those experiencing more debilitating eco-anxiety that is impacting daily functioning.